The semantic structure of accuracy in eyewitness testimony - Gustafsson, Philip U.; Sikström, Sverker; Lindholm, Torun (Frontiers in Psychology, 2024)
In two studies, we examined if correct and incorrect statements in eyewitness testimony differed in semantic content. Testimony statements were obtained from participants who watched staged crime films and were interviewed as eyewitnesses. We analyzed the latent semantic representations of these statements using LSA and BERT. Study 1 showed that the semantic space of correct statements differed from incorrect statements; correct statements were more closely related to a dominance semantic representation, whereas incorrect statements were more closely related to a warmth semantic representation. Study 2 only partially replicated these findings, but a mega-analysis of the two datasets showed different semantic representations for correct and incorrect statements, with incorrect statements more closely related to representations of warmth, abstractness and tentativeness. Given the critical role of eyewitness testimony in the legal context, and the generally low ability of fact-finders to estimate the accuracy of witness statements, our results strongly call for further research on semantic content in correct and incorrect testimony statements.Language enables us to share information and recount events that we have experienced. This ability is crucial in courtrooms, where eyewitnesses commonly testify to what they have seen during criminal events. However, witnesses can lie or misremember, which makes it important to evaluate the accuracy of a testimony. Given the centrality of language in communication, it is not surprising that researchers have attempted to find verbal cues to identify if a witness is lying (see DePaulo et al, 2003), or to tie a suspect to a threat letter (Nini, 2018). In this study, we analyse the verbal content of testimonies from eyewitnesses and examine how correct and incorrect statements might differ semantically.Although much research on accuracy in eyewitness testimonies concerns deception detection (for meta-analyses, see